LDC poverty alleviation and the Doha Development Agenda : is tourism being neglected? - Honeck, Dale ([WTO] [Washington]US, 2008)
Notes tourism's economic and trade importance for least developed countries and addresses opportunities for poverty alleviation. Attempts to find reasons for the apparent neglect of tourism in the Doha Development Agenda. Discusses missed opportunities to address infrastructure and other issues.